Pengaruh Kualitas Produk, Harga dan Citra Merek, terhadap Minat Beli Produk Kecantikan Scarlett di Wilayah Jabodetabek - Bebyzha Bunga Agachi; Hasyim Hasyim (STIKes Ibnu Sina Ajibarang, 2024)
This investigation intends to conclude the effect of thing quality, cost and brand picture on revenue in purchasing Scarlett's pervasive things in the Jabodetabek district. The dependent variable is Buy Interest, while the free factors are item quality, cost, and brand image. Individuals who have utilized Scarlett Lighting up items and are keen on buying them in the Jabodetabek region make up the number of inhabitants in this review. This study chooses an example of 129 respondents utilizing a non-likelihood examining strategy in light of deliberate testing. Using a 4-point Likert Scale, assessments of public sentiment were disseminated to complete the data collection process. Information assessment systems use different direct break faith evaluations. At Scarlett Lighting up things in the Jabodetabek region, the findings of this investigation demonstrate that the nature of the product has a significant impact on buy revenue, that the cost of the product has an impact on buy revenue, and that the brand image has an impact on buy revenue. Furthermore, the quality of the product, the cost of the product, and the brand image all have a positive impact on buy revenue.